Firm performance, corporate governance and executive compensation in Pakistan. Issue 18 (15th April 2018) - Sheikh, Muhammad Fayyaz; Shah, Syed Zulfiqar Ali; Akbar, Saeed
ABSTRACT: This study examines the effects of firm performance and corporate governance on chief executive officer (CEO) compensation in an emerging market, Pakistan. Using a more robust Generalized Method of Moments (GMM) estimation approach for a sample of non-financial firms listed at Karachi Stock Exchange over the period 2005–2012, we find that both current- and previous-year accounting performances has positive influence on CEO compensation. However, stock market performance does not appear to have a positive impact on executive compensation. We further find that ownership concentration is positively related with CEO compensation, indicating some kind of collusion between management and largest shareholder to get personal benefits. Inconsistent with agency theory, CEO duality appears to have a negative influence, while board size and board independence have no convincing relationship with CEO compensation, indicating board ineffectiveness in reducing CEO entrenchment. The results of dynamic GMM model suggest that CEO pay is highly persistent and takes time to adjust to long-run equilibrium.